2022
DOI: 10.1038/s41598-022-12356-5
|View full text |Cite
|
Sign up to set email alerts
|

Shift of the storm surge season in Europe due to climate variability

Abstract: Along the European coasts, changes in the timing of the storm surge season are analyzed. Using 10 long-term tide gauges located in western Europe, a consistent spatio-temporal shift emerged in the storm surge season between 1950 and 2000. Temporal shifts are positive (later events) in the North, negative (earlier events) in the South. Extreme surge events occurred about 4 days/decade later in northern Europe, and 5 days/decade earlier in southern Europe. Such a tendency is similar to the one already reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…Extreme storm surges tend to occur earlier in the year in the south (Portugal/Spain) than in the north (English Channel, UK). A consistent spatio-temporal shift of the timing of the storm surge season over the 2 nd half of the 20th century has recently been reported (Roustan et al, 2022). The storm surge season has tended to occur earlier along the Atlantic coasts of Europe south of 50°N, at an average pace of around 5 days/decade (e.g., a 25-day shift over 1950-2000).…”
Section: Past Sea Level Changessupporting
confidence: 59%
See 1 more Smart Citation
“…Extreme storm surges tend to occur earlier in the year in the south (Portugal/Spain) than in the north (English Channel, UK). A consistent spatio-temporal shift of the timing of the storm surge season over the 2 nd half of the 20th century has recently been reported (Roustan et al, 2022). The storm surge season has tended to occur earlier along the Atlantic coasts of Europe south of 50°N, at an average pace of around 5 days/decade (e.g., a 25-day shift over 1950-2000).…”
Section: Past Sea Level Changessupporting
confidence: 59%
“…Extreme significant wave heights are projected to be significantly larger (up to +40%) at the end of the century under the SSP5-8.5 scenario due to the consideration of mean SLR and tides (Arns et al, 2017;Chaigneau et al, 2023) with implications on wave setup and runup and thus on projections of ESLs. In addition, recent studies have shown, on a global scale and more specifically for Europe, that historical trends in storm surges (Calafat et al, 2022;Reinert et al, 2021;Roustan et al, 2022;Tadesse et al, 2022) and tides (Pineau-Guillou et al, 2021) have been comparable in magnitude to the historical mean SLR trend.…”
Section: Projections Of Dynamic Changes In Extremesmentioning
confidence: 96%
“…Our estimates of circular mean annual phase indicate that for most of the tide gauges in our global analysis, the ASLC peaks during the fall season, which overlaps with the most active storm seasons in the Pacific and Atlantic basins (Oey & Chou, 2016;Roustan et al, 2022). To identify where the phase deviates from its mean over time, we map the circular standard deviation of the phase (Figure 5b).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, at larger scale, Roustan et al. (2022) showed that extreme surge events occurred about 4 days/decade later in northern Europe, and 5 days/decade earlier in southern Europe, still on the 1950–2000 period.…”
Section: Introductionmentioning
confidence: 99%